The relationship between team empowerment and team performance - Mohamad Hafifi Hafiz, Mohamad Saupi (2014)
This study is about the relationship between team empowerment and team performance is assessed in telecommunication industry. The objectives for this study are to identify the relationship between team empowerment and team performance and also to identify the impact of team empowerment on team performance. For this study come out based on the problem statement which is most of the company employee does not have an opportunity to share their own opinion. So, because of that, this study want to identify either the team empowerment have all authority and leave an impact to the team performance. The scope of this study is around the team employee whose work at telecommunication industry located at eastern coastal regions but only focusing at downtown area to be the respondent of this study. Down town are include location at Kuantan, Pahang, Kuala Terengganu, Terengganu, and Kota Bharu, Kelantan. For the data were obtained from the survey questionnaires and sending by email. Total sample of 66 respondents out of 80 telecommunications companies were used in this study. For the result of this study has been identified that there are significant relationship between team empowerment and team performance